The Ilongo hacenderos in Negros Occidental, 1850-1898. - Villanueva, Jocelyn M.
This is a descriptive study that attemps to know the major factors that led to the coming of the Ilongos, particularly those from Jaro and Molo areas, who provided the "big push" in the development of the sugar industry in Negros Occidental. This study also tries to identify effects of their coming in the development of Negros Occidental., Development in Iloilo in the 1850's resulted to the going to Negros Occidental of Ilonggos. Among these are commercialization of agriculture brought about by the opening of Iloilo port, decline of the weaving industry, displacement of Ilongo traders by the Chineses, and greater incentives given to sugar production. Furthermore, the coming of the Ilongo hacenderos also affected the economic, socio-political, and cultural aspects of Negros Occidental. These are the rise of haciendas, emergence of a monocrop economy, exploitation of sugar workers, rise in the population of the province among others.